2023
DOI: 10.1155/2023/8791362
|View full text |Cite
|
Sign up to set email alerts
|

The Microbial Terroir of the Nemea Zone Agiorgitiko cv.: A First Metataxonomic Approach

Abstract: Vitis vinifera L. cv. Agiorgitiko is one of the most popular indigenous wine grape varieties in Greece, cultivated almost exclusively in the Nemea Protected Designation of Origin (PDO) zone. Here, the microbiota of soil, grapes, and wine, during controlled (CF) and spontaneous (SF) fermentations of Agiorgitko cv. from three vineyards in the PDO Nemea zone were explored, using both classical microbiological analysis and metataxonomics to get evidence about the microbial terroir of the PDO Nemea zone. The classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 84 publications
1
0
0
Order By: Relevance
“…In fact, both PCoA and sPLS-DA analyses showed that samples are mainly grouped according to the VL ( Figure 5 ). These results are consistent with those reported in other studies where it was demonstrated that the diversity of the microbial community is influenced by geographical location of vineyards ( Bokulich et al, 2014 ; Mezzasalma et al, 2017 ; Kioroglou et al, 2019 ; Papadopoulou et al, 2022 ; Kazou et al, 2023 ). Similar results were also obtained by other authors who have reported that VL has a greater impact on the fungal community than the state of ripeness ( Kioroglou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…In fact, both PCoA and sPLS-DA analyses showed that samples are mainly grouped according to the VL ( Figure 5 ). These results are consistent with those reported in other studies where it was demonstrated that the diversity of the microbial community is influenced by geographical location of vineyards ( Bokulich et al, 2014 ; Mezzasalma et al, 2017 ; Kioroglou et al, 2019 ; Papadopoulou et al, 2022 ; Kazou et al, 2023 ). Similar results were also obtained by other authors who have reported that VL has a greater impact on the fungal community than the state of ripeness ( Kioroglou et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%